Willingness analysis of middle-aged and older people’s participation in reverse mortgage schemes - Chen, Ching-Yi; Wang, Hsi-Chuan (International Journal of Strategic Property Management, 2024)
Enabling older adults to age at home is an urgent issue. This study focuses on the attitudes of middle-aged and older people (MAOP) in the capital cities of Taiwan, which are characterised by expensive housing prices and living costs, to examine their preferences for reverse mortgage (RM) schemes. The stated preference method and conditional multinomial logit model are utilised for analysis. The study simulates the total payment duration (TPD) and monthly payment amounts (MPA) to determine the market share of MAOPs’ choices regarding terms. The results indicate that MAOPs tend to opt for RM schemes when they have children, partly enhancing the preference toward the long-term alternative (AL). Increasing the MPA has a positive effect on the market share of the AL scheme, but the amount must be increased to 90% to replace the market share of non-participation schemes significantly. The experimental design of this study could serve as a reference for future RM scheme designs. The findings suggest that there should be more alternative funding sources in an ageing society, particularly through revitalising housing assets, to promote ageing in place.